PERANAN TRANSAKSI PERDAGANGAN LUAR NEGERI DAN ENDOSEMEN DALAM PRODUKTIVITAS DAN PEREKONOMIAN - Raspita, Desni (Universitas Muhammadiyah Palembang, 2021)
International trade encourages individual countries to specialize in the production of goods in which that country has comparative advantages. In the case of constant-cost, there will be full specialization of production, while in the case of increasing-cost there is incomplete specialization. What needs to be remembered here is that specialization itself does not bring benefits to society unless it is accompanied by the possibility of exchanging the products for other goods that are needed. developing countries, namely new technology. The problem of technology transfer or transfer of technology from developed countries to developing countries is the most discussed topic in both scientific circles and international negotiations between groups of developing countries and groups of developed countries. Technology transfer is seen as one of the keys to successful development in developing countries. Indonesia's dependence on international trade as the engine of driving the national economy is quite large. According to Salvatore (2007), one of the economic activities that cannot be separated from international trade is the activity of capital flows, both in and out of a country. When international trade activities occur in the form of export and import activities, there is a high probability that there will be a shift in production factors from the exporting country to the importing country due to differences in costs in the international trade processKeywords: Foreign Trade, Developing Countries, Endocement, Economy